Consultancy for LDC projects - Fritz Huhle (Intereconomics, 1973)
How much and what kind of development consulting the industrial states provide for the less developed countries (LDCs) must depend on the structure of the reciplent country and the specific needs for advice ensuing from it. Constant consultation on development issues and development programmes for the whole national economy may be wanted or only advice on individual development projects. The two forms are connected insofar as individual projects must dovetall with an overall plan.
Keywords: 330; Development Policy